The Effect of Earnings Management and Corporate Governance Mechanism to Corporate Social Responsibility Disclosure: An Empirical Study at Public Companies in Indonesia Stock Exchange - Lilik Handajani; Sutrisno Sutrisno; Grahita Chandrarin (The Indonesian Journal of Accounting Research, 2013)
This research examines the effect of earnings management and corporate governance mechanism on corporate social responsibility disclosure. The proportion of independent boards of directors, institutional ownership, and audit committee are used as proxies for corporate governance mechanism. We test our hypothesis on 67 public companies listed in Indonesia Stock Exchange that disclose corporate social responsibility activities for the period of 2005 to 2007. Our empirical tests are consistent with our hypothesis that earnings management and the existence of audit committee are significantly positively associated with corporate social responsibility disclosure even after controlling for firm size and type of industry. This results indicate that corporate social responsibility becomes a part of managerial entrenchment strategy for opportunistic management behavior to gain stakeholders supports. The existence and expanding role of audit committee which is integrated with corporate action plays an important role in assuring the accountability strategy and the implementation of corporate social responsibility. These findings may be of interest to policy makers. The obligations to disclose corporate social responsibility information also needs to be followed by other supporting policies to avoid firms’ opportunistic behavior. Finally, the findings suggest that integrating corporate governance into corporate social responsibility implementation and reporting need to be improved.